Precambrian alkaline-ultramafic/carbonatite volcanism at Qagssiarssuk, South Greenland. - Stewart, J. W. (Meddelelser om Grønland, 1970)
An outburst of alkaline-ultramafic/carbonatitic volcanic activity took place at Qagssiarssuk in the early Gardar period (about 1300 m.y.). High level volcanic structures which have been preserved include the remnants of pyroclastic cones and the uppermost parts of diatremes, some of which did not penetrate to the surface. There are many features which recall the carbonatite volcanoes of East Africa and Zambia, including the presence of flows of carbonatitic material. As a consequence of faulting and subsequent erosion, crystalline basement rocks are exposed nearby. They are penetrated by tuffisite diatremes and other minor intrusions, comagmatic with the efTusive rocks, but corresponding to a depth of at least half a kilometre. The igneous rock types belong to three main groups: (i) monchiquite - alnöite - mica-peridotite, (ii) melilite-rock (a high-level equivalent of uncompahgrite) and (iii) mica-pyroxenite. In addition, a concealed body of carbonatite is directly indicated by blocks of sövite, and other material, in the pyroclastics. An episode of calcitic carbonatization was followed by ankeritic carbonatization. Carbonatization of the melilite-rock was particularly intense. Barytes and fluorite were also introduced. The volcanism was characterized by an abundance of volatiles and it is probable that fluidized systems were developed. Granitic basement rocks adjacent to the intrusions underwent progressive potash feldspathization with the ultimate production of almost pure potash feldspar rock, locally intrusive (Na2O = 0.50 % ; K2O = 13.50 %).